Determining the Comparative Effectiveness of Chemical Method and Mechanical Methods of Breaking Seed Dormancy in Solanum aethiopicum - Jenipher Tuhirirwe (Uganda Christian University, 2025)
Dormancy of seeds in solanum aethiopicum groups thus gilo and shum, hinders uniform germination. This leads to disturbances in the harvesting schedules and the overall yields. This study evaluated the effectiveness of chemical methods (Gibberellic acid, potassium nitrate), and mechanical methods (hot water and mechanical scarification) in breaking seed dormancy in these varieties (shum and gilo). Gibberellic acid is a plant hormone based chemical, which is responsible for plant cell elongation and combating the effects of ABA. Potassium nitrate is a nutrient based chemical containing potassium and nitrates essential for plant growth. The seeds of various accessions of shum and gilo were presoaked in different concentrations of Gibberellic acid (GA3) and, potassium nitrate (KNO3) i.e. GA3 (500mg/l, 300mg/l,700mg/l) and KNO3 (0.25%,0.75%,1.0%) for 24 hours. Hot water treatment, the seeds were treated with water heated up to 80 °C for 5 minutes and mechanical scarification, seeds were scratched with sand paper carefully and then rinsed. The sowing of seeds were followed, where they were sown in petridishes lined with wet cotton wool and arranged in a 4X3 factorial experiment using CRD design. The outcomes indicated that when treatments compared, Gibberellic acid 500mg/l with 92.5% germination and mechanical scarification with 70% germination are the effective treatments for breaking seed dormancy in shum, while gilo responds same way to mechanical scarification and hot water treatment. While comparing the effectiveness of chemical and mechanical methods in breaking seed dormancy in shum and gilo, the chemical treatments outperformed the mechanical treatments more especially in shum with 58.2% germination and MGT (3.9 versus 8.3) and higher germination percentage (58.2% versus 46.0%). For gilo variety however, mechanical methods resulted into higher GP (34.8 versus 23.4) but indicated similar GVI and slower MGT (8.3). When comparisons are made within the treatments, GA 500mg/l significantly increased germination percentage in shum with 82.89% mean GP compared to gilo that indicated 39.37% mean Gp. Mechanical scarification also improved germination significantly with 70% mean GP in shum compared to hot water that resulted in no significant difference between hot water and mechanical scarification. Moreover, shum exhibited a significantly lower mean germination time with 3.2 days compared to KNO and distilled water. Therefore, null hypothesis one was rejected as the results show significant differences (p<0.001) in effects of chemical treatments on seed performance in both shum and gilo with GA 500mg/l being the best and reject the second null hypothesis as mechanical methods indicated significant differences in the effects of hot water and mechanical scarification on germination parameters with p<0.001.
Undergraduate